2021
DOI: 10.3390/genes12050712
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Expression of Reprogramming Factor OCT4 Ameliorates Myelination Deficits and Induces Striatal Neuroprotection in Huntington’s Disease

Abstract: White matter atrophy has been shown to precede the massive loss of striatal GABAergic neurons in Huntington’s disease (HD). This study investigated the effects of in vivo expression of reprogramming factor octamer-binding transcription factor 4 (OCT4) on neural stem cell (NSC) niche activation in the subventricular zone (SVZ) and induction of cell fate specific to the microenvironment of HD. R6/2 mice randomly received adeno-associated virus 9 (AAV9)-OCT4, AAV9-Null, or phosphate-buffered saline into both late… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Such results reveal undeniable defect of the microstructure of brain tissues. DTI was used as a biomarker of myelination to evaluate the effect of a reprogramming factor injection in R6/2 mice ( Yu et al, 2021 ). Continuous Time Random Walk (CTRW) model on the same mice showed decreased Dαβ and α parameters, highlighting increased tortuosity and axonal density of corpus callosum ( Gatto et al, 2019 ).…”
Section: Mri and Mrs Findings In Genetic Mouse Models Of Hdmentioning
confidence: 99%
“…Such results reveal undeniable defect of the microstructure of brain tissues. DTI was used as a biomarker of myelination to evaluate the effect of a reprogramming factor injection in R6/2 mice ( Yu et al, 2021 ). Continuous Time Random Walk (CTRW) model on the same mice showed decreased Dαβ and α parameters, highlighting increased tortuosity and axonal density of corpus callosum ( Gatto et al, 2019 ).…”
Section: Mri and Mrs Findings In Genetic Mouse Models Of Hdmentioning
confidence: 99%
“…In a 2021 study by Yu et al, the reprogramming effects of Oct4 were investigated using R6/2 mice, a Huntington's disease model [22]. Two weeks after Oct4 injection, an increase in Nestin+ cells, a marker of neural stem cells, was observed.…”
Section: Disease or Injured Animal Modelsmentioning
confidence: 99%
“…These induced neurons were identified as calretinin+ and Neun+ neurons, and they were detected for up to 36 weeks. Moreover, these induced neurons displayed electrophysiological functionality and integrated into local circuits, allowing them to receive inputs from presynaptic neurons [22]. Regarding the cell of origin, Zhang C. L.'s group suggested astrocytes as the source.…”
Section: Healthy Animal Modelsmentioning
confidence: 99%
“…Studies have demonstrated that more functionally induced neurons and oligodendrocytes can be obtained by in vivo reprogramming ( Farhangi et al, 2019 ; Wu et al, 2020 ; Zhou et al, 2020 ). In vivo reprogramming has been attempted in neurological diseases, such as Parkinson’s disease ( Theodorou et al, 2015 ; Niu et al, 2018 ) and Huntington’s disease ( Wu et al, 2020 ; Yu et al, 2021 ). Experiments have shown that reactive glial cells can be converted into functional neurons using a single TF NeuroD1 fate in vivo in brain injury and AD models ( Guo et al, 2014 ).…”
Section: Potential To Cure For Alzheimer’s Disease Using In...mentioning
confidence: 99%